Changes in Resting-State Functional Connectivity of the Hippocampus Following Cognitive Effort Predict Memory Decline at Older Age—A Longitudinal fMRI Study - Oren, Noga; Ash, Elissa L.; Shapira-Lichter, Irit; Elkana, Odelia; Reichman-Eisikovits, Osnat; Chomsky, Lior; Lerner, Yulia (Frontiers in Aging Neuroscience, 2019)
Identifying older adults at risk for memory impairment is an important goal for initiating early treatment and prevention strategies. We examined the resting-state functional connectivity (RSFC) of older and younger adults before and after cognitive effort as a marker for subsequent memory decline, focusing on the connectivity between the left anterior hippocampus (laHC) and the posterior hippocampi (pHC). Results showed that for younger adults, post-effort increases in laHC-pHC connectivity were related to increases in connectivity between the laHC and the hubs of the default mode network. However, for older adults, post-effort increases in the RSFC of laHC-pHC were related to decreases in the connectivity of the laHC and right precentral gyrus. Thus, the correlation between intra-HC and inter-HC RSFC was altered with cognitive effort and aging. Importantly, older adults who had lower post-effort RSFC between the laHC and the pHC demonstrated a decline in an episodic memory 2 years later. Hence, the change in intra-HC RSFC following cognitive effort was able to predict subsequent memory function with aging in our sample.